Penggunaan Media Pembelajaran Audio Visual untuk Meningkatkan Motivasi Belajar Siswa Kelas X A SMAN 6 Palu - Nirwan Nirwan (Jurnal Kreatif Online, 2021)
The purpose of this study was to determine the increase in student motivation through the use of Audio Visual learning media in class X A students of SMAN 6 Palu in the 2018/2019 academic year. This study consisted of 2 cycles, each of which went through the planning, implementation, observation and reflection stages. The subjects of this study were 34 students of class X A SMAN 6 Palu. The data collection technique in this study was the observation method to determine the student's learning motivation in Indonesian subjects using audio-visual learning media. The data analysis technique used is quantitative descriptive analysis. Based on the results of the research, it was found that using audio-visual media could increase the learning motivation of class X A students of SMAN 6 Palu in Indonesian subjects. The data from the first cycle showed that students who have very good learning motivation were 15 people (46.87%), have good motivation were 10 people (31.25%) and have enough motivation as many as 7 people (21.88%). In the second cycle, there were an increase, where students who had very good motivation increased to 30 people (93.75%) and students who had good motivation were 2 people (6.25%).